15. Scalp somatosensory evoked potentials recordings after human subthalamic and pedunculopontine tegmental nucleus stimulation. Issue 4 (April 2016) - Insola, A.; Mazzone, P.; Valeriani, M.
Abstract : The study aimed to investigate the pathways activated by deep brain stimulation (DBS). Four patients, suffering from parkinson disease (PD), underwent DBS electrode implant in the pedunculopontine (PPTg) nucleus (2 patients) and in the Subthalamic (STN) nucleus (2 patients) for neuromodulation. Somatosensory evoked potentials (SEPs) were recorded from the scalp to either median nerve or DBS electrode stimulation. The PPTg stimulation evoked a parietal negative and a frontal positive response at a latency of 3 ms, corresponding to the N20 and P20 potentials to median nerve stimulation, respectively. The STN stimulation evoked a negative potential at a latency of 6 ms in both the parietal and frontal electrodes. Our findings show that the electrical stimulation of the PPTg electrode contacts activate an oligosynaptic (probably lemniscal) pathway, while the scalp responses to STN stimulation are mediated by a polysynaptic pathway.